Oceanic dispersal in a sedentary reef shark (Triaenodon obesus): Genetic evidence for extensive connectivity without a pelagic larval stage - Whitney, N.; Robbins, William; Schultz, J.; Bowen, B.; Holland, K. (Blackwell Publishing, 2012)
Aim Most reef fishes are site-attached, but can maintain a broad distribution through their highly dispersive larval stage. The whitetip reef shark (Triaenodon obesus) is site-attached, yet maintains the largest Indo-Pacific distribution of any reef shark while lacking the larval stage of bony (teleost) fishes. Here we use mitochondrial DNA (mtDNA) sequence data to evaluate the enigma of the sedentary reef shark that maintains a distribution across two-thirds of the planet. Location Tropical Pacific and Indian Oceans. Methods We analysed 1025base pairs of the mtDNA control region in 310 individuals from 25 locations across the Indian and Pacific Oceans. Phylogeographic and population genetic analyses were used to reveal the dispersal and recent evolutionary history of the species. Results We resolved 15 mtDNA control region haplotypes, but two comprised 87% of the specimens and were detected at nearly every location. Similar to other sharks, genetic diversity was low (h=0.550±0.0254 and p = 0.00213 ± 0.00131). Spatial analyses of genetic variation demonstrated strong isolation across the Indo-Pacific Barrier and between western and central Pacific locations. Pairwise F ST comparisons indicated high connectivity among archipelagos of the central Pacific but isolation across short distances of contiguous habitat (Great Barrier Reef) and intermittent habitat (Hawaiian Archipelago). In the eastern Pacific only a single haplotype (the most common one in the central Pacific) was observed, indicating recent dispersal (or colonization) across the East Pacific Barrier. Main conclusions The shallow haplotype network indicates recent expansion of modern populations within the last half million years from a common ancestor. Based on the distribution of mtDNA diversity, this began with an Indo-West Pacific centre of origin, with subsequent dispersal to the Central Pacific and East Pacific. Genetic differences between Indian and Pacific Ocean populations are consistent with Pleistocene closures of the Indo-Pacific Barrier associated with glacial cycles. Pairwise population comparisons reveal weak but significant isolation by distance, and notably do not indicate the high coastal connectivity observed in other shark species. The finding of population structure among semi-contiguous habitats, but population connectivity among archipelagos, may indicate a previously unsuspected oceanic dispersal behaviour in whitetip reef sharks. © 2011 Blackwell Publishing Ltd.